Physical Function and All-Cause Mortality in Older Adults Diagnosed with Cancer: A Systematic Review and Meta-Analysis - Garcia-Hermoso, A (Oxford University Press, 2021)
Background: Physical function is an independent predictor of numerous chronic diseases, but its association with all-cause mortality in older adults diagnosed with cancer has received little attention. The aim of this study was to conduct a systematic review and meta-analysis on the prospective association between physical function and all-cause mortality in older adults diagnosed with cancer. Methods: Two authors systematically searched MEDLINE, EMBASE, and SPORTDiscus databases. Prospective studies reporting associations of baseline physical function with all-cause mortality in patients aged 60 years or older diagnosed with any type of cancer were included. Hazard ratios (HR) with associated 95% confidence intervals (CI) were extracted from studies for all-cause mortality, and pooled HRs were then calculated using the random-effects inverse-variance model with the Hartung-Knapp-Sidik-Jonkman adjustment. Results: Data from 25 studies with 8109 adults diagnosed with cancer aged 60 and older were included in the study. Higher levels of physical function (short physical performance battery, HR = 0.44, 95% CI 0.29-0.67; I2 = 16.0%; timed up and go, HR = 0.40, 95% CI 0.31-0.53; I2 = 61.9%; gait speed, HR = 0.41, 95% CI 0.17-0.96; I2 = 73.3%; handgrip strength: HR = 0.61 95% CI 0.43-0.85, I2 = 85.6%; and overall, HR = 0.45 95% CI 0.35-0.57; I2 = 88.6%) were associated with a lower risk of all-cause mortality compared to lower levels of functionality. Neither age at baseline nor length of follow-up had a significant effect on the HR estimates for lower all-cause mortality risk. Conclusion: Physical function may exert an independent protective effect on all-cause mortality in older adults diagnosed with cancer. © 2020 The Author(s).